HUBUNGAN PENGETAHUAN DAN SIKAP PASIEN DENGAN UPAYA PENCEGAHAN PENULARAN TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS MUARO KUMPEH KABUPATEN MUARO JAMBI TAHUN 2015 - susilawati susilawati; Dwi Yunita Ramdhani; Elis Suryani Purba (Universitas Baiturrahim, 2016)
Background: Tuberculosis (pulmonary TB) is an infectious disease directly caused by tuberculosis bacteria (Mycobacterium tuberculosa) which is transmitted through the air (droplet nuclei) when a tuberculosis patient coughs and spray saliva containing the bacteria are inhaled by others during breathing.Method: This research is a quantitative research with cross sectional design. Population in this research is 63 respondents, the sample amounted to 58 respondents. The sampling technique using total sampling technique. The study was conducted on 7 April to 13 April 2015.Result: The results showed that the respondents have a high knowledge of the prevention of transmission of Pulmonary TB either as many as 15 people (55.6%) , and respondents who have low knowledge to the prevention of transmission of Pulmonary TB unfavorable as many as 25 people (80.6%). Chi-square test results showed that there is a relationship between knowledge and prevention of pulmonary TB transmission in Puskesmas Muaro with a p-value of 0.010 (p <0.05).Respondents who have a good attitude to the prevention of transmission of Pulmonary TB either as many as 18 people (78.3%), respondents who have a poor attitude to the prevention of transmission of Pulmonary TB unfavorable as many as 32 people (91.4%). Chi-square test results showed that there was a significant relationship between attitudes to the prevention of pulmonary TB transmission in Puskesmas Muaro KumpehKabupaten Muaro Jambi 2015 with a p-value of 0.000 (p <0.05).